ANALISIS MENGENAI MATERI MUATAN PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2003 TENTANG PROSEDUR MEDIASI PENGADILAN - Bintoro, Rahardi Wasi; Sudrajat, Tedi (Faculty of Law, Universitas Jenderal Soedirman, 2008)
These days the solving of dispute by jurisdiction gets the critics from the practitioner and the jurist. The role and function of jurisdiction were assumed overloaded, wasting time, expressive, less responsive to the public interest, and also too formal and technical. There were various concepts that already offered to make the jurisdiction more simple, quick and light expenses. One of the concept which have been offered and now applying is the mediation institute in the civil the court system through PERMA No. 2 year 2003. The background of this regulation is because of the application of article 130 HIR is not effective. It changes the voluntary to the compulsory system by using the mediation institute. Now the party must used the mediation before entering the litigation. Kata kunci: Jurisdiction, dispute and mediation.